Classificações de risco gestacional e desigualdades sociais em saúde - Garcia, Érica Marvila (2017)
The classification of gestational risk has been used as an instrument to identify the risk factors and, consequently, leading the planning of the care given to the pregnant woman, making it a regulator of prenatal care. Faced with this issue, the social inequalities in health are clearly relevant and appear as indicators for maternal health. The objective of this study was to analyze the gestational risk classifications and social inequalities in health in two regions of Espírito Santo state, Brazil. Cross-sectional studies with representation of the population of the Unified Health System (SUS). The analyzes were carried out starting from the conjugation of the data of 1035 puerperae from the Greater Vitória Metropolitan Region (RMGV) - Espírito Santo (ES) and 742 puerperas from the São Mateus Microregion (MRSM) - ES, based on absolute and relative frequency calculations and a 95% confidence interval. The levels of concordance between two methods of gestational risk classification (Ministry of Health (MS), Pan American Health Organization (PAHO)) and self-report were verified through the Kappa and Kappa tests adjusted for prevalence.Was also madethe bivariate analysis using the Chi-square association test of Yates and The Multivariate Logistic Regression for the variables with significance level lower than 20%, remaining in the final model the explanatory variables with a level of significance lower than 5%. The factors that most contributed to the classification of women in gestational risk levels in the MS method were: unsafe marital status (19.2%), inadequate pregestational weight (17.7%), smoking and alcohol (17.7%), the interpartal interval (25.4%) and exposure to occupational risk (27.0%), while in the PAHO gestational risk classification were oral health problems during gestation (42.2%). In both methods, the history of abortion (18.5% - MS and 22.8% - PAHO), previous uterine surgery (49.8% - MS and PAHO), inadequate and very inadequate weight gain (67,1%), urinary tract infection (27.8%), anemia (29.5%) and gestational hypertension (10.2%) were the ones that most contributed to the classification of gestational risk. The agreement between the method of risk classification of MS and PAHO was moderate (Kappa = 0.45, p-value <0.05) and poor between the MS method and self-report (Kappa 0.05; pvalue <0.05) and PAHO and self-report (Kappa 0.01; p-value <0.05). The association between high gestational risk was classified according to the MS method and the place of residence of the woman in the RMGV-ES (OR = 1.74, 95%, CI: 1.32-2.28), the head of the woman in the family (OR = 3.03, 95%, CI: 1.64-5.61), schooling of the family heads less than five years old (OR = 1.58, 95%, CI: 1.14-2.20), and Receiving the "Bolsa Família" social benefit (OR = 1.46, 95%, CI 1.04-2.03). The conditions that emerge in the assessment of gestational risk, when controlled or eliminated, can contribute to a pregnancy without many interventions and with favorable outcomes. However, it is necessary to broaden the scope of the social factors that make up the risk classification, since the study showed other social factors that may also be the producers of gestational risk.